2012
DOI: 10.1143/jjap.51.094303
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Transient Energy Transport and Energy Balance in a Single-Level Quantum Dot System

Abstract: The decay of ThC (212Bi) to ThC' (212Po) has been studied by coincidence techniques and those gamma radiations emitted from the 21zPo nucleus have been distinguished from other gamma rays in the thorium decay series. An estimate of intensities has enabled the assignment of multipole orders to some transitions. The branching ratio of 212Bi and the half-life of the ground state of 212Po were re-measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…1 Many computational works have also been performed, and found that the time-dependent currents through nanoscale systems often oscillate around the value of the stationary current after sudden switching-on of voltage. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Such current oscillations decay with time and then the systems reach the steady states. This non-steady phenomenon, which often emerges in the case of a weak coupling between an electrode and a scattering region, is a consequence of roundtrip motions of electrons between them.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1 Many computational works have also been performed, and found that the time-dependent currents through nanoscale systems often oscillate around the value of the stationary current after sudden switching-on of voltage. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Such current oscillations decay with time and then the systems reach the steady states. This non-steady phenomenon, which often emerges in the case of a weak coupling between an electrode and a scattering region, is a consequence of roundtrip motions of electrons between them.…”
mentioning
confidence: 99%
“…This non-steady phenomenon, which often emerges in the case of a weak coupling between an electrode and a scattering region, is a consequence of roundtrip motions of electrons between them. [7][8][9][10][12][13][14] This roundtrip motion originates from the interference between electrons in the scattering region before applying the voltage and electrons in the electrodes after applying voltage.…”
mentioning
confidence: 99%
See 3 more Smart Citations